Companies Value of Indonesia Telecommunications Sector And Influencing Factors - Roosmawarni, Anita; Sa'diyah, Halimatus; Eferyn, Krissantina (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
The increase in public demand for telecommunications facilities provides opportunities for telecommunications companies, especially in the company's value, which the weight of total assets can measure. This study aims to determine the effect of the Current Ratio, Debt To Asset Ratio, Return On Equity, Return On Investment on firm value. The object of research is the telecommunications sector company with data used in 2014-2020. This study uses quantitative research methods with multiple linear regression data analysis for panel data and is assisted by the STATA 15 analysis tool. The results obtained that the best model is the common effect model (CEM) with t-test results in the Debt To Asset Ratio and Return On Equity variables having a significant effect on firm value with each t value of 0,003 and 0,001. Still, for the variables, the Current Ratio and Return On Investment do not substantially impact firm value with t-value 0,133 and 0,437. Meanwhile, simultaneously, these four variables significantly affect firm value with a significance value off of 0,000. The value of the R square obtained is 0,7031, which shows a significant effect of the independent variable on the dependent variable of 70,31%. These results indicate that if the company wants to increase its total assets, it must increase its current assets and attract investors to invest more capital so that the profits received by the company can be improved